Claiming the Guarantor and Avoiding the Actual Debtor in a Contract of Dayn: A Comparative Juristic Perspective - Al Asmari, Saad bin Ali Abdullah (Journal of Islamic and Religious Studies, 2022)
Although the legitimacy of demanding a loan from the guarantor instead of the debtor is often permitted by the scholars, it is causing many social and judicial confusions in modern times because people deliberately neglect it, which makes the guarantor liable for their debts, and he must bear the burden of payment which is causing the bail to be closed. Sometimes, without knowing the guarantor's financial status, the court orders him to pay the debt and this decision greatly affects his family life. In this research, attention has been drawn to the need to revise some of the rulings that Islamic scholars have stated at a particular time, and they were correct as of that time, but due to the change in the situation, those rulings have become obsolete at the present time, are not appropriate for the time and place. This research consists of an introduction, the conditions of guarantee, words related to guarantee, justification of guarantee and its wisdom, the sayings of scholars in the issue of justification of demanding loan from guarantor instead of debtor, legal way of not binding the sponsor, etc. are included. In conclusion, there are study findings and recommendations from the discussion.